A conventionalist theory of the Business Model in the context of business creation for understanding organizational impetus - Verstraete, Thierry; Jouison-Laffitte, Estèle (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2011)
The Business Model is a buzzword that appeared with the famous start-ups. The authors adopt a conventionalist approach to explain its nature. They show that a convention implies a movement that brings into being the entrepreneurial phenomenon, and with it, the seeds of an organization. In real terms, the entrepreneur must go prospecting to convince the owners of the resources he needs for his project to bring them to him, so that he can make an offer of value to the market. They will only join him if they can identify a potential remuneration (both for the offer as a whole and for their own efforts). In other words, the Business Model (BM) is a social artifact that explains organizational impetus, for resources can only be obtained (and hence organized) if a convention is born between the partners. In so doing, the convention makes the entrepreneurial phenomenon observable. In the context of business creation, the BM is this convention. It is, in some ways, a medium for expressing the shared world view of the various stakeholders who will constitute the firm.